The Mapping of Disaster Readiness of SSB (The Disaster Ready Schools) in The Coastal Area of Padang City, Indonesia - Anwar, Syafri (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose of this research was to identify the level of readiness of SSB (the Disaster Ready Schools) in the coastal area of Padang City especially in the red zone area in facing the disaster, especially earthquake and tsunami. Some variables of SSB are: the school community knowledge about the disaster, the disaster response skills, the school policies/SOP, the emergency response plans, and the resource mobilization. This research was descriptive research using observation, interviews and questionnaires in data collection. The data were analyzed using the percentage formula to determine the tendency of respondents. The research population was the SSB in the red zone area. The samples were determined by using purposive sampling technique to choose the schools and proportional random sampling technique to choose the respondents. The results of the research are: 1). the school community knowledge about the disaster tends to be good (3.1), 2). the disaster response skills tend to be good (3.2). 3). not all schools have the good school policies/SOP, 4). In general, no schools have the emergency response plans/the resource mobilization. Based on the calculation of the indicators achievement level, it can be concluded that the readiness of SSB in the coastal area of Padang City especially in the red zone area in facing the disaster is still low. It is proved by only a limited number of SSB that have good readiness. The research recommends: a need of serious disaster mitigation efforts on the part of policy makers. The efforts must be done according to program and continuously. In the attempts given,a variety of innovative activities should be done, such as doing the socialization and disaster response simulation periodically, the celebration of the disaster day, the celebration of the earth day, the celebration of the environmental day, and the empowerment of community (especially schools community), as well as the provision of facilities and infrastructure.